Respuesta :

Answer: [tex](7)^(^6^x^)=(7)^(^6^x^+^3^)[/tex]

Step-by-step explanation:

[tex]49^3^x=343^2^x^+^1[/tex]

[tex](7^2)^(^3^x^)=(7^3)^(^2^x^+^1^)[/tex]

[tex](7)^(^6^x^)=(7)^(^6^x^+^3^)[/tex]

Up to this points, is the equation in terms of base, from now on, I'm going to try to solve it.

Since we have the same base, exponents must be equal

[tex]6x=6x+3\\6x-6x=3\\0=3[/tex]

Since we lost our variable, there's nothing to solve for. Therefore, this has no solution.

Answer:

first is 7, second is B, and 3rd is D no solution

Step-by-step explanation:

got answers on edge

ACCESS MORE